Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.3 - Integrated Review - Summary on Solving Quadratic Equations: 23

Answer

$x_{1}= \sqrt{12} = 2\sqrt{3}$ and $x_{2}= -\sqrt{12} = -2\sqrt{3}$

Work Step by Step

Given $4x^2-48=0$ $1.)$ Divide by 4 both sides: $4x^2-48=0 \longrightarrow x^2-12=0$ $2.)$ Apply difference of two squares: $x^2-12=0 \longrightarrow (x+\sqrt{12})(x-\sqrt{12})=0$ Therefore the solutions are $x_{1}= \sqrt{12} = 2\sqrt{3}$ and $x_{2}= -\sqrt{12} = -2\sqrt{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.